Improvement of Quantitative Single-Photon Emission Computed Tomography Image Quality by the New Step-and-Shoot Scan Mode - Hiroki Yamamoto; Ami Sasaki; Mizuki Osaka; Koji Shirakawa; Morio Seino; Takaaki Matsuhashi; Yasuyuki Takahashi; Tsutomu Zeniya; Shota Hosokawa; Masataka Narita; Masahiko Aoki (Radiation, 2022)
The step-and-shoot (SS) mode and continuous mode are currently used for single-photon emission computed tomography (SPECT) scan mode, and a new scan mode that combines both modes, step-and-shoot plus continuous (SSC) mode, was developed. It is expected to allow a shorter scan time and lower injected dose because the SSC mode is more sensitive than the SS mode. We confirmed the image quality of this scan mode, including various quantitative correction methods for scatter (SC), attenuation (AC), and resolution recovery (RR) in a phantom study and clinical case study. Image quality was evaluated by the count, contrast-to-noise ratio (CNR), and percent of the coefficient of variation (%CV). Independent of the correction methods, the count, CNR, and %CV of the SSC mode were superior to those of the SS mode. The ACSCRR was the best method, with a maximum increased rate of 66.4% in counts and 57.8% in CNR for the 13-mm sphere and 19.6% in CNR for other sphere sizes. The %CV for the SSC mode was the best for AC and ACRR, which was at 15.1%. With regards to attaining short bone SPECT scan time, the combination of the SSC mode and ACRR or ACSCRR demonstrated the best physical performance.